Assessment of the Therapeutic Communication Skills of Clinicians with Patients in the University of the Philippines Manila College of Dentistry/Gianna Marie L. Marabut. - Marabut, Gianna Marie L.
Introduction: Dental curricula is observed to focus more on the technical skills and cognitive knowledge of dental students, without great emphasis on communication skills which are vital to patient care. The study aimed to assess the communications skills of clinicians with patients in the University of the Philippines Manila College of Dentistry (UPCD).